Theory of competing excitonic orders in insulating WTe_2 monolayers - Kwan, YH; Devakul, T; Sondhi, SL; Parameswaran, SA (American Physical Society, 2021)
We develop a theory of the excitonic phase recently proposed as the zero-field insulating state observed near charge neutrality in monolayer WTe$_2$. Using a Hartree-Fock approximation, we numerically identify two distinct gapped excitonic phases: a spin density wave state for weak but non-zero interaction strength $U_0$, and spin spiral order at larger $U_0$, separated by a narrow window of trivial insulator. We introduce a simplified model capturing essential features of the WTe$_2$ band structure, in which the two phases may be viewed as distinct valley ferromagnetic orders. We link the competition between the two phases to the orbital structure of the electronic wavefunctions at the Fermi surface and hence its proximity to the underlying gapped Dirac point in WTe$_2$. We briefly discuss collective modes of the two excitonic states, and comment on implications for experiments.